Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s11136-017-1777-0
|View full text |Cite
|
Sign up to set email alerts
|

An empirical comparison of the measurement properties of the EQ-5D-5L, DEMQOL-U and DEMQOL-Proxy-U for older people in residential care

Abstract: PurposeThis study aimed to empirically compare the measurement properties of self-reported and proxy-reported (in cases of severe cognitive impairment) generic (EQ-5D-5L) and condition-specific (DEMQOL-U and DEMQOL-Proxy-U) preference-based HRQoL instruments in residential care, where the population is characterised by older people with high rates of cognitive impairment, dementia and disability.MethodsParticipants were recruited from seventeen residential care facilities across four Australian states. One hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 40 publications
2
41
0
2
Order By: Relevance
“…Previous research has highlighted the challenges in quality-of-life assessment in this group [39]. These challenges relate to the level of missing data, validity of either selfor proxy-reports, and the ability of available measures to capture relevant disease and intervention impacts.…”
Section: Methodological Challenges and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has highlighted the challenges in quality-of-life assessment in this group [39]. These challenges relate to the level of missing data, validity of either selfor proxy-reports, and the ability of available measures to capture relevant disease and intervention impacts.…”
Section: Methodological Challenges and Future Researchmentioning
confidence: 99%
“…Equally, it may relate to the sample reporting on this measure. Research suggests individuals with mild cognitive impairment can provide valid self-reports and for those that cannot, proxy reports may be used [39]. However, research is needed to identify the threshold for utility measure selfcompletion and to test methods of combining self-complete and proxy data, which may include adjustment of values or mapping.…”
Section: Methodological Challenges and Future Researchmentioning
confidence: 99%
“…Construct validity was examined by comparing utility scores. First, pairs of utility scores generated by different PBMs completed by the same proxy respondent at the same time point were compared (eg, informal carers' EQ-5D-5L-proxy and DEMQOL-Proxy-U responses) using Spearman's rank-order correlation (where correlation ,0.3 was considered weak, 0.3 to ,0.5 moderate, 0.5 to ,0.6 strong, and $0.6 very strong 4 ) and Bland-Altman plots (differences between 2 utility values generated by 2 different PBMs plotted against the mean of the utility values). Second, utility scores generated from the same PBM completed by different respondents at the same time point were compared (eg, informal-carer EQ-5D-5L-proxy vs formal-carer EQ-5D-5L-proxy or resident-completed EQ-5D-5L) using Spearman's rank-order correlation and Bland-Altman plots (first, differences between 2 utility values recorded at the same time point were plotted against the mean, and second, differences between the change in utility values between 2 time points were plotted against the mean at the first time point).…”
Section: Construct Validitymentioning
confidence: 99%
“…2 One study showed almost half (48%) of respondents with dementia self-reported having no problems on any EQ-5D dimension (ie, "perfect health"), 3 which seemed unlikely to accurately reflect the respondents' true health state, given the instrument's assessment of such areas as mobility and pain. However, proxy assessors can have different perceptions of another's capabilities and health state, 2,4 perhaps particularly for more unobservable or subjective dimensions (eg, pain or anxiety/ depression vs functional ability), and exhibit additional sources of bias that could differ between individuals. For example, a relative's response might reflect additional emotional burden when compared with formal or employed carers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation